The many assassinations of Samir, the Seller of Dreams - Nayeri, Daniel (Levine Querido, 2023)
Saved from a stoning by the monks he lives with, twelve-year-old Sogdian orphan Omar is sold to traveling tradesman Samir and becomes a part of his caravan along the Silk Road. Moving from place to place, Omar, who is now called Monkey, learns that Samir is a dishonest salesman who cons his customers. Though Monk doesn't approve of Samir's dealings, he participates out of a sense of duty. Soon though, he learns that Samir has angered one too many people and that assassins are after him. Monk hopes to secure his freedom from Samir's service by saving his life six times and hoping they both make it through the ordeal alive.